2013
DOI: 10.1128/cmr.00076-12
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium Pathogenicity and Virulence

Abstract: SUMMARYCryptosporidiumis a protozoan parasite of medical and veterinary importance that causes gastroenteritis in a variety of vertebrate hosts. Several studies have reported different degrees of pathogenicity and virulence amongCryptosporidiumspecies and isolates of the same species as well as evidence of variation in host susceptibility to infection. The identification and validation ofCryptosporidiumvirulence factors have been hindered by the renowned difficulties pertaining to thein vitroculture and geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
380
2
24

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 479 publications
(412 citation statements)
references
References 276 publications
6
380
2
24
Order By: Relevance
“…Considered a zoonosis of utmost importance, cryptosporidiosis has a worldwide distribution and can infect about 170 species of animals including mammals, birds, reptiles, and amphibians (SANTÍN, 2013;FAYER, 2008;BOUZID et al, 2013). Currently, about 26 species of Cryptosporidium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Considered a zoonosis of utmost importance, cryptosporidiosis has a worldwide distribution and can infect about 170 species of animals including mammals, birds, reptiles, and amphibians (SANTÍN, 2013;FAYER, 2008;BOUZID et al, 2013). Currently, about 26 species of Cryptosporidium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Till now, more than 26 species of Cryptosporidium, are recognized based on host specificity, morphology and molecular biology studies [1].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown some important parasite antigens and proteins such as gp40/15, P23, gp40, gp15, and gp900 that have important roles in invasion and adhesion of the parasite to host cells (5). These proteins can induce production of some specific host immune responses against the infection, which can be detected by antibodies in serum of humans, who are infected with Cryptosporidium parvum (6). Accordingly, production of these immunogenic proteins as recombinant proteins and DNA vaccines provides a valuable strategy for the diagnosis of infection and immunize animals (3,(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%